Observations on the ex situ perfusion of livers for transplantation. Issue 8 (14th March 2018) - Watson, Christopher J. E.; Kosmoliaptsis, Vasilis; Pley, Caitlin; Randle, Lucy; Fear, Corinna; Crick, Keziah; Gimson, Alexander E.; Allison, Michael; Upponi, Sara; Brais, Rebecca; Jochmans, Ina; Butler, Andrew J.
Abstract : Normothermic ex situ liver perfusion might allow viability assessment of livers before transplantation. Perfusion characteristics were studied in 47 liver perfusions, of which 22 resulted in transplants. Hepatocellular damage was reflected in the perfusate transaminase concentrations, which correlated with posttransplant peak transaminase levels. Lactate clearance occurred within 3 hours in 46 of 47 perfusions, and glucose rose initially during perfusion in 44. Three livers required higher levels of bicarbonate support to maintain physiological pH, including one developing primary nonfunction. Bile production did not correlate with viability or cholangiopathy, but bile pH, measured in 16 of the 22 transplanted livers, identified three livers that developed cholangiopathy (peak pH < 7.4) from those that did not (pH > 7.5). In the 11 research livers where it could be studied, bile pH > 7.5 discriminated between the 6 livers exhibiting >50% circumferential stromal necrosis of septal bile ducts and 4 without necrosis; one liver with 25‐50% necrosis had a maximum pH 7.46. Liver viability during normothermic perfusion can be assessed using a combination of transaminase release, glucose metabolism, lactate clearance, and maintenance of acid‐base balance. Evaluation of bile pH may offer a valuable insight into bile duct integrity and risk of posttransplant ischemic cholangiopathy. Abstract : The authors describe a series of ex situ normothermic liver perfusions in which they examine biochemical markers of hepatocyte and cholangiocyte biochemistry in an effort to predict posttransplant viability.